Evaluating ICT utilization in education administration and management during the COVID-19 outbreak in Pakistan: An empirical review - Chandio, Abdul Rahim (Univeritas Papua, 2021)
This study aims to evaluate the utilization of ICT in education administration and management in a Pakistan context during the pandemic outbreak. Adoption of information and communication technologies (ICTs) has digitalized the learning process where education organizations were administrated by means of wireless-based instructions, electronic pedagogy, and online assessment in order to continue the educational activities while the government halted the physical appearance in education institutions. Data collection has been carried by three public universities in which teachers and general administration of these institutions participated to discover their intention to use the assigned technology to administrate organizations’ policies in the way to disseminate the respective service delivery. Survey questionnaires were used, and 178 respondents’ feedback was secured to analyze the study that was carried out via SPSS version 24 and validation OF hypotheses measured by means of regressions and correlations. Moreover, proposed factors like intention to use, perceived ease of ease, perceived usefulness, social influence, and Users’ expectations were used. A theoretical approach was inculcated to encircle the UTAUT and TAM model to determine the adoption of the innovative system education management during the pandemic outbreak in the country.